2013
DOI: 10.1186/1749-8090-8-47
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis for fast track protocol failure

Abstract: BackgroundThe introduction of fast-track treatment procedures following cardiac surgery has significantly shortened hospitalisation times in intensive care units (ICU). Readmission to intensive care units is generally considered a negative quality criterion. The aim of this retrospective study is to statistically analyse risk factors and predictors for re-admission to the ICU after a fast-track patient management program.Methods229 operated patients (67 ± 11 years, 75% male, BMI 27 ± 3, 6/2010-5/2011) with use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
(47 reference statements)
2
20
1
Order By: Relevance
“…Another factor of objection may be the length of ICU stays in the overall group and Group N. There was about 4 days of ICU stay for the overall group, which can be determined to be too long. Fast track surgery is used increasingly, and successful outcome results have been reported (1,16). Our analysis marks the point that even with a long ICU stay, there is a considerable rate of ICU readmission, especially in the high-risk groups.…”
Section: Discussionmentioning
confidence: 79%
“…Another factor of objection may be the length of ICU stays in the overall group and Group N. There was about 4 days of ICU stay for the overall group, which can be determined to be too long. Fast track surgery is used increasingly, and successful outcome results have been reported (1,16). Our analysis marks the point that even with a long ICU stay, there is a considerable rate of ICU readmission, especially in the high-risk groups.…”
Section: Discussionmentioning
confidence: 79%
“…We know in patients undergoing cardiac surgery that ASA>3, NYHA>3 and operation time>267 min are independent predictors of fast-track protocol failure [1]. Especially advanced age and left ventricular dysfunction (EF<35%) found to be significant preoperative predictors of failure.…”
Section: Discussionmentioning
confidence: 99%
“…These studies mainly have shown the benefits of fast track protocol in cardiac surgery. However, Kiessling et al reported that risk factors that could predict the fast track protocol failure in cardiac surgery, are ASA class >3, NYHA class > III and operation time >267 min (8).…”
Section: Discussionmentioning
confidence: 99%